STUDI ANALITIKAL PERILAKU DAN KINERJA STRUKTUR RANGKA DINDING PENGISI DENGAN BUKAAN SENTRIS - I Putu Agus Putra Wirawan; I Ketut Diartama Kubon Tubuh; I Gede Gegiranang Wiryadi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
This study aims to compare the open frame structure (OF) with the centric perforated infill wall frame structure (IF) with reinforcement around the opening. Validation of the model on the results of laboratory tests was carried out. Next, a simple frame model is made to make an equation for the width of the diagonal strat. Single-stage IF is also made with an aperture ratio of 10% to 60% at 10% intervals and diagonal strat angles of 33°, 39°, 45°, 51°. The infill wall is made by modeling the diagonal strat and shell elements. After obtaining the strat width formula, it continues with applying the formula in modeling a three-story frame structure with varying diagonal strat angles. The results obtained are IF modeling with shell and strat diagonal elements that can follow the results of laboratory tests. From the analysis of the width of the diagonal strat, the formula Wco = (d/4tanØ)·Cc, where d is the length of the diagonal; Cc is the coefficient of stiffness of the wall (Cc = 1.2022r2-2.0953r + 1.045); r is the opening wall ratio; Ø is a diagonal angle. The application of the strat width formula shows the behavior of the strat model coincides with the shell element model. The strength of the structure increases 57%-86% after the addition of walls. The difference in drift ratio shows that the diagonal strat angle is inversely proportional to the strength of the structure that occurs.